Towards Drinking Water Security in India : Lessons from the Field - World Bank (Washington, DC, 2017)
India being a vast and diverse country, we face many challenges in ensuring reliable, sustainable safe drinking water supply to rural households of the country. Though, in terms of provision of safe drinking water, we have covered more than 90 percent of the rural households, according to the National Sample Survey Office (NSSO) 65th round survey 2008-09, the authors have to recognize that much remains to be done to improve levels of service delivery, water quality and sustainability. Though chemical contamination of drinking water is being tackled today in the National Rural Drinking Water Program (NRDWP), bacteriological contamination, which is more dangerous and also more prevalent, has to be systematically measured and tackled. This requires convergence with the total sanitation campaign to ensure an open defecation free and clean environment. slightly more than 30 percent of rural households obtain their drinking water supply through taps which are more convenient, saving time and labour specially of women and children. however, this varies widely ranging from less than 5 percent in Uttar Pradesh and Bihar to more than 80 percent in Tamil Nadu and Himachal Pradesh. With the help of Water and Sanitation Program (WSP), the department of drinking water and sanitation has collected some models of good practices from different parts of the country. Care has been taken to ensure these are drawn from as many states as possible. In addition, the good practices identified cover a variety of areas ranging from improved service delivery, operation of multi-village schemes, efficient operation and maintenance, ensuring water quality, measures to ensure source sustainability, pioneering efforts for waste water management, effective communication practices that have been adopted and institutional reforms at state level that have been tried out.